Effect of gallic acid on Aspergillus carbonarius growth and ochratoxin A production - Romero, Stella Maris (2010)
The aim of the present study was to investigate the gallic acid influence on Aspergillus carbonarius growth and ochratoxin A (OTA) biosynthesis. A mixed inoculum was used in Czapek Yeast Extract Agar and growth and OTA production was observed at 100 to 500 mg/l of the phenolic compound. Slower colony growth rates and longer lag phases were observed with increasing concentration and 500 mg/l was totally inhibitory for A. carbonarius growth. OTA production decrease was observed even at the lower concentration assayed. Gallic acid could be used as a natural antimicrobial for the control of ochratoxigenic A. carbonarius.